Perbandingan Mutu dan Profil Disolusi Tablet Griseofulvin Merek Dagang Generik - Gumala, Azhoma; Lucida, Henny; Salman, Salman (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2022)
Abstract: Griseofulvin is an active pharmaceutical ingredient in Biopharmaceutic Classification Systems Class II and the price of the dosage form from commercial brands four times higher than the generic. A comparative study on physical properties and dissolution profiles between generic and commercial brands of griseofulvin tablets has been conducted to assess whether there is difference between their qualities. The pharmaceutical properties were assessed based on the Indonesian and the United State Pharmacopeias. Results showed that the tablets fulfilled the requirements for size uniformity, weight uniformity (0.5995± 0.0075) gram - (0.6989±0.0080) gram, friability 0.08-1.10 %, hardness (10±0.7746) - (19.6±0.9165) kg/cm2, disintegration time 07.12 - 17.17 minutes with drug content of 94.20 - 99.67%. The commercial brand griseofulvin tablets A1& A2 and generic B1 met the official specification for physical characteristics. Results of dissolution test for commercial brand A1 & A2 and generic B1 showed that griseofulvin had T60min (Q ≤ 70%) and the dissolution test profiles did not follow neither first order, Higuchi, Korsmeyer Peppas, nor Langenbucher kinetic models (r < 0,95). The dissolution test for griseofulvin tablet A1 met the USP specification, T90min (Q ≥ 75%) with the release mechanism follow Langenbucher kinetic model. Abstrak: Griseofulvin merupakan zat aktif golongan Sistem Klasifikasi Biofarmasetik kelas II dengan perbedaan harga antara tablet merek dagang lebih mahal hingga empat kalinya dibandingkan tablet generik. Uji disolusi terbanding dilakukan untuk melihat adakah perbedaan mutu yang signifikan antar tablet tersebut. Metode evaluasi mutu dilakukan sesuai dengan ketentuan Farmakope Indonesia dan USP. Hasil evaluasi mutu fisik tablet meliputi keseragaman ukuran, keseragaman bobot yaitu (0,5995± 0,0075) – (0,6989±0,0080) gram, kerapuhan 0,08 - 1,10%, kekerasan (10±0,7746) - (19,6±0,9165) kg/cm2, & waktu hancur 07.12 - 17.17 menit dan penetapan kadar 94,20 - 99,67%, memenuhi ketentuan Farmakope Indonesia. Profil disolusi tidak mengikuti model kinetika orde satu, Higuchi, Korsmeyer Peppas, ataupun Langenbucher (r < 0,95). Hasil uji disolusi tablet A1 yang dilakukan berdasarkan USP memenuhi persyaratan T90 min (Q ≥ 75%) dan memiliki profil disolusi mengikuti persamaan Langenbucher (r>0,95). Keywords: Profil disolusi, tablet griseofulvin, mutu tablet, model matematika